Evaluation of brownification mitigation potential of a wetland constructed in a managed Swedish forest - Evaluation of brownification Osby - Djerf, Henric (Kristianstad University, 2021)
Material collected in Jonstorp north of Osby with the aim of studying how a constructed wetland reduces the colour of the water. Contains chemical and hydrological data collected in field. Chemical data consists of analysis results from an accredited laboratory and hydrological data is reproduced in Excel format.

Data from the projekt Evaluation of brownification mitigation potential of a wetland constructed in a managed Swedish forest.

Chemical_data.xlsx contains a summary over the chemical analyses made by of the accredited lab Synlab.
Flow_recording.xlsx contains the elevation recorded by ISCO autosampler at inflow to the wetland and actual flow measurement to convert the elevation to a flow.
Trace_data.xlsx contains the reading of rhodamin at the outflow point.

csv_data.zip contains the excel-files converted to csv format.

Material insamlad i Jonstorp norr om Osby med syftet att studera hur en konstruerad våtmark minska färgen på vattnet. Innehåller kemiska och hydrologisk data insamlad i fält. Kemiska data består av analysresultat från ackrediterat laboratorium och hydrologisk data återges i Excel-format.

Data från projektet Utvärdering av begränsningspotentialen för brunifiering av en våtmark anlagd i en svensk produktions skog.

Chemical_data.xlsx innehåller sammanställning över de kemiska analyser som gjorts av det ackrediterade labbet Synlab.
Flow_recording.xlsx innehåller höjden registrerad av ISCO autosampler vid inflöde till våtmarken och faktisk flödesmätning för att omvandla höjden till ett flöde.
Trace_data.xlsx innehåller avläsningen av rhodamin vid utflödespunkten.

csv_data.zip innehåller excel-filerna konverterade till csv-format.
Utvärdering av begränsningspotentialen för brunifiering av en våtmark anlagd i en svensk produktions skog - Utvärdering av brunifiering Osby
Keywords: bog; våtmark; wetland; våtmarker; Land use; Markanvändning; Rhodamine WT; Rhodamine WT; Brownification; Brunifiering; Environmental Sciences; Miljövetenskap; Environment; Miljö